Premature death risk from young adulthood incarceration - Witteveen, D (Taylor & Francis, 2021)
Drawing the National Longitudinal Survey of Youth 1979 data, a comprehensive treatment model indicates a strong positive influence of incarceration on premature death risk. Models adjust for numerous covariates of mortality, including demographics, family background, and a range of health and behavioral indicators measured during childhood, as well as selection into incarceration (“treatment”). This study expands extant research by observing much longer panel data, closer to the mortality curve. The main treatment effect reveals risk of premature death by one’s mid-fifties being increased by 13.9 percentage-points. Results also indicate that young adulthood incarceration shortens lives equally for Blacks and non-Blacks.